Essays in post-critical philosophy of technology - Héder, Mihály; Nádasi, Eszter (Vernon series in philosophy., 2019)
"Technology, in all its forms, has had and continues to have an indisputable impact on society and culture. Philosophy of technology seeks to understand this impact and the meaning of technology for society and culture. Although its origins can be traced back to the Greeks, it wasn't until the late 19th century to the beginning of the 20th century that it gained ground as a philosophical discipline. Now more than ever it is considered an essential philosophical enterprise. 'The Budapest Workshop on Philosophy of Technology' was a lively and successful event that sought to discuss, reflect on and apply this branch of philosophical inquiry to both historical and contemporary examples. Importantly, the contributors' methodological approaches were influenced by, although not limited to, Michael Polanyi's term 'post-critical'. Moving beyond the rigidity of past approaches, the selected essays were driven by two lines of inquiry, what has been the historical role of technology in social and scientific change? And, how can a 'post-critical' approach enhance and extend our understanding of philosophy of technology? This edited volume begins by exploring the role of technology in social and scientific developments from a historical perspective, before moving towards a discussion of philosophy of technology from a 'Post-Critical' epistemic stance. Free from the constraints of previous methodologies, the third part of this work engages with the term 'Post-Critical' in its broadest sense. The contributors to this section consider the phenomenology of the body and the influence of technology on our lives. Finally, the four concluding chapters of this book apply this philosophical approach to a wide range of contemporary problems from Decision Support Systems to Crisis Communication."--Publisher's description